2000
DOI: 10.1108/00070700010327733
|View full text |Cite
|
Sign up to set email alerts
|

Changes in supermarket sales during and after a staged health promotion campaign

Abstract: To test the feasibility of the use of supermarket sales data in evaluating a local point of purchase intervention and to assess the impact of the intervention six and 12 months later. Staged point of purchase intervention pilot study followed by a longitudinal observational study. The study was carried out in one supermarket in Mikkeli, Finland. Foods were classified as healthier or reference products based on their labelled content of salt and saturated fat. The sales of packaged foods containing reduced amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Though not statistically significant (P=.082), the intervention resulted in a 3.6% increase in the percentage of sales from tagged items. This research supports previously published POP nutrition information strategies that successfully impacted food-purchasing behaviors in grocery stores (17)(18)(19)(20)(21)(22). Three of these studies were conducted in large urban grocery stores (17,20,22).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Though not statistically significant (P=.082), the intervention resulted in a 3.6% increase in the percentage of sales from tagged items. This research supports previously published POP nutrition information strategies that successfully impacted food-purchasing behaviors in grocery stores (17)(18)(19)(20)(21)(22). Three of these studies were conducted in large urban grocery stores (17,20,22).…”
Section: Resultssupporting
confidence: 86%
“…Studies examining the effect of POP information on food purchasing behaviors in grocery stores, restaurants, universities, and the workplace have recently been reviewed (11,13). In grocery stores, of the ten interventions that focused primarily on information strategies (14)(15)(16)(17)(18)(19)(20)(21)(22)(23), six of the studies showed increased sales for, at most, 50% of the targeted food items (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Community relations seemed most relevant for single stores. Interventionists frequently perceived strong community relationships as potential motivators for retailers [23, 27, 31, 40], or a way to gather community support [41, 46]. In two cases, retailers perceived robberies as a threat to their own and interventionists’ safety [21, 40]; turning the community into a barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Legislation was discussed little. In one study, the interventionists perceived governmental legislation as a potential facilitator for the implementation of interventions [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation